Correlation between the size of the incisive papilla and the distance from the incisive papilla to the maxillary anterior teeth - Soo-Yeon Shin; Tae Hyung Kim (Elsevier, 2016)
Background/purpose: The incisive papilla remains relatively constant in position and is frequently used as an anatomic landmark for anterior teeth. Several attempts have been made to use the incisive papilla as guides to arrange maxillary anterior teeth for edentulous patients. The aim of the present study was to determine the relationship between maxillary anterior teeth and the incisive papilla, while comparing the findings with the classical estimate value. Materials and methods: Horizontal distances between the labial surface of the central incisors and the incisive papilla [the distance from the labial surface of the central incisors and the posterior border of the incisive papilla (CPIP), the distance from the labial surface of the central incisors and the anterior border of the incisive papilla (CAIP), and the distance from the labial surface of the central incisors and the center of the incisive papilla (CCIP)] and the size of the incisive papilla (SIP) were measured by a digital caliper on the stone casts formed for 103 dentate persons. The Pearson correlation coefficient was used to investigate and quantify the correlation, while simple linear regression analyses were conducted to determine the strength of the association between the variables (α = 0.05). Results: Pearson correlation coefficients for SIP and the distance between the labial surface of the central incisors and the incisive papilla (CPIP, CAIP, and CCIP) were significant (P < 0.05). A simple linear regression analysis of the data was performed, which showed that SIP contributed significantly to the prediction of the distances between the labial surface of the central incisors and the incisive papilla (CPIP and CCIP; P < 0.05). Conclusion: Using regression methods within the population tested, it was determined that the distance between the labial surface of the central incisors and the incisive papilla could be predicted by the size of the incisive papilla.